analisis kadar protein dan vitamin c pada sambal-ikan sebelum dan sesudah diolah - Aisyi, Dinda Rohadatul; Santoso, Hari; Lisminingsih, Ratna Djuniwati (FMIPA UNISMA, 2019)
Fish-Chili- sauce processed by a mixture of cayenne pepper (Capsicum frutescens), tomatoes (Lycopersicum esculentum) and Deles fly fish (Decapterus macrosoma) as fast-food sources of protein that is favored by the public. The purpose of this study are to determine the protein and vitamin C levels of fish-chili-sauce before and after processing. The research method are used completely randomized design with two treatments, namely treatment 1 measured levels of protein and vitamin C before processing; treatment 2 measures the levels of protein and vitamin C after processing. The protein test was performed using the Kjeldahl method with a Spectrophotometer Technique. Vitamin C testing uses the Iodimetry method. The results showed that protein levels of fish before processing = 19.31% and = 20.24 mg/100g of vitamin C. After processing the fish protein content Â = 15.63% and = 16.28 mg/100g of vitamin C levels. Decreased fish protein levels and vitamin C levels were thought to be due to the length of processing time. The results of the analysis of the T-Test Pairs showed that there are no significant difference in the protein content of fish-chili-sauce before and after processing, but it tended to decrease. The results of the analysis of the Pairs T-Test showed that there are significant differences in the levels of vitamin C of fish-chili-sauce before and after processing.ABSTRAKSambal-ikan hasil olahan campuran cabai rawit (Capsicum frutescens), tomat (Lycopersicum esculentum) dan ikan layang Deles (Decapterus macrosoma) sebagai sumber protein cepat saji yang digemari oleh masyarakat. Tujuan penelitian ini untuk mengetahui kadar protein dan vitamin C sambal-ikan sebelum dan sesudah diolah. Metode penelitian di gunakan Rancangan Acak Lengkap dengan 2 perlakuan yaitu perlakuan 1 mengukur kadar protein dan vitamin C sebelum diolah; perlakuan 2 kadar protein dan vitamin C sesudah diolah. Uji protein dilakukan menggunakan metode Kjeldahl dengan Teknik Spektrofotometer. Uji vitamin C menggunakan metode Iodimetri. Hasil penelitian menunjukkan kadar protein 19,31% dan kadar vitamin C 20,24 mg/100g. 15,63%. dan kadar vitamin C16,28 mg/100g. Penurunan kadar protein ikan dan kadar vitamin C diduga karena lamanya waktu proses pengolahan. Hasil analisi uji T-Test Pairs menunjukkan tidak ada perbedaan yang signifikan pada kadar protein sambal-ikan sebelum dan sesudah diolah, namun cenderung mengalami penurunan. Hasil analisis uji T-Test Pairs menunjukkan ada perbedaan yang signifikan pada kadar vitamin C sambal-ikan sebelum dan sesudah diolah.